Efek Ekstrak Bawang Dayak (Eleutherine palmifolia (L.)Merr) dan Ubi Ungu (Ipomoea batatas L) terhadap Penurunan Kadar Kolesterol dan Trigliserida Darah pada Tikus Jantan - Kusuma, Anjar Mahardian; Asarina, Yupin; Rahmawati, Yeni Indah; Susanti, Susanti (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2016)
Bawang Dayak (Eleutherine palmifolia (L.)Merr) and Ubi Ungu (Ipomoea batatas L.) are potential medicinal plant in lowering cholesterol. This study aims to measure the effect of bawang dayak extract and ubi unggu extract on lowering cholesterol and triglyceride blood levels in male rats fed with 10 ml/Kg BW quail egg yolk. The cholesterol and triglyceride blood levels of rats were measured with 50, 100 and 200 mg/Kg BW dose variations for each extract for 14 days. Cholesterol and triglyceride levels were measured at day 15th by ‘Multicare’. As controls were rats fed with 1,26 mg/Kg BW simvastatin, 1 % (b/v) Na-CMC, and normal diet. The data was analyzed by Anova statistical tests and LSD (α = 0,05). The result shows that both extracts can reduce cholesterol and triglyceride blood levels with 200mg/Kg BW dose. Bawang dayak extract can reduce cholesterol and triglyceride blood levels to 80.8 ± 9.2 mg/dL and 95 ± 7.9 mg/dL, respectively. Ubi ungu extract can reduce cholesterol and triglyceride blood levels to 72 ± 8.2 mg/dL and 86.4 ± 4.3 mg/dL, respectively.